Fake Populism or Real Populism: Pork Barrel Policy as Political Corruption in House of Representative During 2009- 2013 - JATI, WASISTO (Jurnal Studi Pemerintahan, 2013)
This article aims to analyze the practice of pork barrel politics in the level of Indonesia legislature tiers and its politicalmanagement campaign. Since 2004, electoral democracy already delegate to the common people to chosen theirrepresentation directly through general election in the level executive and legislative. Those conditions oblige politician andpolitical parties to approaching the commons in order to obtain their vote and popularize both actors into public. Theparadigm of research is a pork barrel politics. This paradigm supports to understand and analyze the corruption symptomsi.e. politico corruption in legislative tier and electoral-corruption in political-campaign which become chronic problems inthis country. Result of research has showed populism is pivotal key which triggered up politician and parties to corruption inorder to persist their political tenure and funding their political cost in pursue to re-elect again in second office terms. Nomatter their corruption practice that implicate to budgeting fraud. Both actors take political favor to disguise within socialaids following the governmental policy, so that, they hindered from corruption accusation. Finally, this paper wants torecommend legal improvement into our budgeting cycle wherein there are public participation to watch it and moralimprovement to politician and parties to reducing their corruption if they wants to become truly populist politician figureinto public.